Influence of chemical curing technique on the properties of fly ash aggregates prepared without conventional binders - Suresh, G.Venkata; Karthikeyan, J. (Journal of Structural Engineering, 2024)
In any conventional concrete, the major volume is occupied by the coarse aggregates only. To fill this volume natural crushed aggregates are generally used and bulk usages of these aggregates lead to depletion of natural resources. In India, according to statistics from 2014-15 nearly 42.37% (73.24 million tons) fly ash generated from thermal power stations are unutilized. Usage of fly ash aggregates into concrete has potential for large scale utilization in the construction industry leading to the reduction of environmental degradation, i.e., effective utilization of fly ash. The conventional existing methods of curing like cold bonding, sintering and autoclaving are experiencing some drawbacks. To overcome these drawbacks, a novel chemical curing technique has been proposed in this paper, the aggregates are cured chemically by immersion in a sodium hydroxide (NaOH) solution prepared with different molar ratios i.e 5M, 8M, 10M, 12M. The present study deals with the influence of chemically cured fly ash aggregates on its physical and mechanical properties and is compared with naturally cured and water cured fly ash aggregates. The strength of Chemical Cured Aggregates (CCA) was found to be 64.93% and 49.03% higher after 7 days and 28 days respectively, when compared to that of Water Cured Aggregates (WCA). The percentage of water absorption of CCA is 4.0% at 7 days and 4.2 % at 28 days.